The Importance of Identification and Analysis of Educational Needs for Investment in Human Capital - Kucharcikova, Alzbeta (Communications - Scientific letters of the University of Zilina, 2014)
Human capital has currently represented significant production input for economies and companies as well. The need for investment is more intense in connection with the massive introduction of science and technology achievement into life and the need for constant innovation. Investments in human capital are made of the funds being invested in education, training, safety and security, health and etc. However, it is mostly the investment in education. Whether the subject of investment is a state, an individual or company, for the investment to be effective, it is necessary to place the identification and analysis of educational needs first. The purpose of this paper is to point out the importance of identification of the educational needs in company conditions, the methods of effective implementation, the accompanying problems and measures to prevent them.